SP0040 Transitional Care – Recommendations for Best Practice. (9th June 2015) - Foster, H.E.
Abstract : Transitional care is an integral component of best practice for young people with paediatric onset rheumatic disease. 'Getting it right' is increasingly regarded as a priority for all health care providers working in paediatric, adolescent and adult rheumatology. This lecture will describe the importance of transitional care and provide an update on the recent multinational, multidisciplinary and multiprofessional initiative from EULAR and PRES to define recommendations for best practice for transitional care for young people with Juvenile Idiopathic Arthritis. These recommendations encompass clinical care, health care service provision, training and research. Disclosure of Interest: None declared